(untitled) (Indian Journal of Chemistry (IJC), 2025)
Marine bioactive compounds have been showing diversified bioactivities such as antifungal, antimicrobial, anticancer, and antiviral. Mutations of KRAS G12C and G12D protooncogenes responsible for colorectal, lung, and pancreatic cancers. KRAS G12C and G12D inhibitors sotorasib, MRTX 1133, and adagrasib showed good anticancer potential. In this research, we screened 2000 marine bioactive compouds from marine database and 1699 molecules showed highest probability as drug like structure. Selected marine compounds were molecular docked against KRAS G12C and G12D using sotorasib and MRTX 1133 as standard structures. In case of KRAS G12C inhibition Halenaquinone, xestoquinone, halenaquinol, and sotorasib showed good docking scores of -11.7 kcal/mol, -11.6 kcal/mol, 11.5 kcal/mol, and -9.1 kcal/mol, respectively. In case of KRAS G12D inhibition Pseudane V, 1,6,10-trihydroxy-8-methyltetracene-5,12-dione, Methylaplysinopsine, and MRTX 1133 showed good docking scores of -11.0 kcal/mol, -9.9 kcal/mol, and 9.7 kcal/mol, and -10.2 kcal/mol, respectively. MD simulation and MMPBSA analysis data showed that RMSD, RMSF, SASA, Rg and hydrogen bond analysis reflected the structural integrity and stability of drug-receptor complex. FMO analysis showed that Xestoquinone and 1,6,10-trihydroxy-8-methyltetracene-5,12-dione represented as soft molecules effective against KRAS G12C and G12D, respectively. This research confirmed the potential of marine ecosystem in the management of cancer by targeting KRAS mutations.